Teaching Basic Quantum Mechanics in Secondary School Using Concepts of Feynman's Path Integrals Method - Fanaro, Maria de Los Angeles (2012)
This paper discusses the teaching of basic quantum mechanics in high school. Rather than following the usual formalism, our approach is based on Feynman’s path integral method. Our presentation makes use of simulation software and avoids sophisticated mathematical formalism. We start by discussing the experimental results that would be observed in an idealized double-slit experiment. With the assistance of software simulations, we focus on the changes observed as the objects’ masses are reduced from macroscopic to atomic values. After that we introduce the basis of quantum mechanics by means of the concepts of path integrals, which henceforth we will call “sum of all alternatives.” Finally, we show how the transition from classical to quantum behavior naturally emerges within the framework of “sum of all alternatives.”